Season of conception in rural gambia affects DNA methylation at putative human metastable epialleles. - Robert A Waterland; Richard Kellermayer; Eleonora Laritsky; Pura Rayco-Solon; R Alan Harris; Michael Travisano; Wenjuan Zhang; Maria S Torskaya; Jiexin Zhang; Lanlan Shen; Mark J Manary; Andrew M Prentice (PLoS Genetics)
Throughout most of the mammalian genome, genetically regulated developmental programming establishes diverse yet predictable epigenetic states across differentiated cells and tissues. At metastable epialleles (MEs), conversely, epigenotype is established stochastically in the early embryo then maintained in differentiated lineages, resulting in dramatic and systemic interindividual variation in epigenetic regulation. In the mouse, maternal nutrition affects this process, with permanent phenotypic consequences for the offspring. MEs have not previously been identified in humans. Here, using an innovative 2-tissue parallel epigenomic screen, we identified putative MEs in the human genome. In autopsy samples, we showed that DNA methylation at these loci is highly correlated across tissues representing all 3 embryonic germ layer lineages. Monozygotic twin pairs exhibited substantial discordance in DNA methylation at these loci, suggesting that their epigenetic state is established stochastically. We then tested for persistent epigenetic effects of periconceptional nutrition in rural Gambians, who experience dramatic seasonal fluctuations in nutritional status. DNA methylation at MEs was elevated in individuals conceived during the nutritionally challenged rainy season, providing the first evidence of a permanent, systemic effect of periconceptional environment on human epigenotype. At MEs, epigenetic regulation in internal organs and tissues varies among individuals and can be deduced from peripheral blood DNA. MEs should therefore facilitate an improved understanding of the role of interindividual epigenetic variation in human disease.